2013
DOI: 10.1159/000354597
|View full text |Cite
|
Sign up to set email alerts
|

Ear Acupressure for Smoking Cessation: Study Protocol for a Randomised Controlled Trial

Abstract: Background: Smoking is the largest preventable cause of death and disease worldwide but smokers often fail to quit due to nicotine withdrawal symptoms. Current available pharmaceutical therapies may assist with smoking cessation but may have side effects. Ear acupressure (EAP) and ear acupuncture have been used for smoking cessation, and some positive results have been reported. The aim of the study is to assess the efficacy and safety of EAP in assisting individuals to quit smoking and/or support them in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The ear points were selected based on existing literature and use in other clinical trials [21]. In general, the point “lung” is used for lung disorders, and “shenmen” is used to calm the mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ear points were selected based on existing literature and use in other clinical trials [21]. In general, the point “lung” is used for lung disorders, and “shenmen” is used to calm the mind.…”
Section: Discussionmentioning
confidence: 99%
“…In this randomized participant-and-assessor-blind clinical trial, noninvasive ear acupressure (EAP) was done on 5 points as recommended in the literature for smoking cessation and used in previous trials (see Protocol [21]). The control intervention was EAP on five points considered as not specific for smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive forms of acupuncture such as laser and magnets are more appropriate for use on premature infants since they prevent creating an entry for infections via the skin [10]. Previous studies have shown the therapeutic benefit of acupuncture in adult populations that are suffering from withdrawal symptoms [11,12]. The National Acupuncture Detoxification Association (NADA) has formulated a standardized ear acupuncture protocol for substance abuse treatment in adults ( Figure 1) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent placebo-controlled study on ear acupuncture, former positive results from non-controlled studies could not be confirmed [40]. However, there are also new promising study results in ear acupressure [41] and hypnosis [42]. …”
Section: Discussionmentioning
confidence: 99%